2017
DOI: 10.1007/s11128-017-1717-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantum steering and entanglement in three-mode triangle Bose–Hubbard system

Abstract: We consider the possibility of generation steerable states in Bose-Hubbard system composed of three interacting wells in the form of a triangle. We show that although our system still fulfills the monogamy relations, the presence of additional coupling which transforms a chain of wells onto triangle gives a variety of new possibilities for the generation of steerable quantum states. Deriving analytical formulas for the parameters describing steering and bipartite entanglement, we show that interplay between tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…In [3][4][5], the authors have shown that the xth power of the entanglement of formation (x ≥ √ 2) and the concurrence (x ≥ 2) satisfy multiqubit monogamy inequalities. Monogamy relations for quantum steering have also been demonstrated in [17][18][19][20][21]. Later, polygamy inequalities were proposed in terms of the αth (0 ≤ α ≤ 1) power of square of convex-roof extended negativity (SCREN) and the entanglement of assistance [14,22].…”
Section: Introductionmentioning
confidence: 99%
“…In [3][4][5], the authors have shown that the xth power of the entanglement of formation (x ≥ √ 2) and the concurrence (x ≥ 2) satisfy multiqubit monogamy inequalities. Monogamy relations for quantum steering have also been demonstrated in [17][18][19][20][21]. Later, polygamy inequalities were proposed in terms of the αth (0 ≤ α ≤ 1) power of square of convex-roof extended negativity (SCREN) and the entanglement of assistance [14,22].…”
Section: Introductionmentioning
confidence: 99%
“…Note, that systems containing Kerr-type nonlinearities have already been considered as a source of entangled states [ 20 , 21 , 22 ]. Systems of two coupled waveguides with Kerr nonlinear medium used in one or both channels have been studied in the context of co- and contra-directional couplers (for review, see [ 23 ]).…”
Section: Introductionmentioning
confidence: 99%
“…They result in truncation of the Hilbert space (nonlinear quantum scissors) [83][84][85][86] and subsequent generation of highly entangled states [77,84,87]. Various forms of quantum correlations such as the entanglement and Einstein-Podolsky-Rosen (EPR) steering were also predicted in short chains of quantum Kerr oscillators [88][89][90][91]. On the other hand, the process of parametric down-conversion analyzed alone without any damping or amplification gives rise to both single-mode squeezing and entanglement between both modes expressed through sub-shot-noise photon-number correlations [92].…”
Section: Introductionmentioning
confidence: 99%